Significance of Liver Zonation in Hepatocellular Carcinoma - Yu, Shizhe; Gao, Jie; Wang, Haoren; Liu, Long; Liu, Xudong; Xu, Yuantong; Shi, Jihua; Guo, Wenzhi; Zhang, Shuijun (Frontiers in Cell and Developmental Biology, 2022)
Liver zonation is fundamental to normal liver function, and numerous studies have researched the microstructure of normal liver lobules. However, few studies explored the zonation signature in hepatocellular carcinoma (HCC). Here, we aimed to investigate the significance of liver zonation in HCC with the help of single-cell RNA sequencing (scRNA-seq) and multi-color immunofluorescence staining. Liver zonation-related genes were extracted from the literature, and a three-gene model was established for HCC prognosis. The model reliability was validated with the bulk RNA and single-cell RNA-level data. To reveal the underlying biological mechanism, we performed function enrichment analysis. The results showed that the signaling pathways of high-risk groups were similar to that of perivenous zones in normal liver, indicating the possible regulating role of hypoxia in HCC zonation. Furthermore, the co-staining results showed that the low-grade tumors lost the zonation features when the high-grade tumors even lost the expression of zonation-related genes, which supported the results obtained from the sequencing data.